Bridging Social Inequality Gaps - Concepts, Theories, Methods, and Tools - Andrzej Klimczuk; Delali Adjoa Dovie (IntechOpen, 2024)
Bridging Social Inequality Gaps - Concepts, Theories, Methods, and Tools focuses on contemporary discussions around multifaceted causes, explanations, and responses to social disparities. The contributors provide studies related to social and cultural dimensions of inequality, economic and technological dimensions of inequality, environmental dimensions of inequality, and political, ethical, and legal dimensions of inequality, as well as a variety of other perspectives on disparities. The volume also covers crucial issues and challenges for the global, national, regional, and local implementation of public policies to reduce inequalities, including innovative actions, projects, and programs focused on achieving the United Nations Sustainable Development Goals (SDGs). The collection includes chapters encompassing research and practical recommendations from various disciplines such as sociology, economics, management, political science, administrative science, development studies, public health, peace and conflict studies, cultural studies, educational studies, communication studies, and social work. This book is an asset to academic and expert communities interested in theories of social inequality as well as effective measurement tools, public services, and strategies. Moreover, the volume helps students, practitioners, and people working in government, business, and nonprofit organizations to build more equitable social relationships.
Keywords: D63; D60; I14; M14; J14; J15; J16; I30; 330; discrimination; diversity management; inequalities; intersectionality; marginalisation; poverty alleviation; social inclusion; social policy; social responsibility; Sustainable Development Goals